Acute lumbosacral hemorrhagic ganglion cyst after transforaminal epidural steroid injection - Dong-Yeong Lee; Young-Jin Park; Kun-Tae Kim; Jeong-Hee Lee; Dong-Hee Kim (Acta Orthopaedica et Traumatologica Turcica, 2018)
Epidural steroid injection is one of the most commonly used non-surgical treatments for degenerative lumbar vertebral disease. Its use has increased as degenerative lumbar vertebral disease has increased in frequency. Concomitant complications are being reported more often. In this report, we report a rare case of iatrogenic hemorrhagic cyst following epidural steroid injection. The patient underwent operative treatment with complete resolution of his symptoms Keywords: Juxtafacet cyst, Ganglion cyst, Hemorrhage, Epidural injection, Complications